Young South African vegetarians: constructing identities and negotiating relationships - Chapman, Sarah (My University, 2015)
This study aimed to explore vegetarian identity and relationships among young South Africans. Food forms a part of every person’s everyday life, not only as it is a biological need but also because practices involving food, the consumption of food and thoughts about food are meaningfully intertwined with cultural norms and socio-political values (Caplan, 1997; Mintz & Du Bois, 2002). The participants in the study were eleven vegetarian individuals living in Johannesburg, most of whom were university students. Data collection was done in two stages including individual semi-structured interviews followed by a focus group to which participants brought vegetarian food tasters to share. The study was done using a qualitative research approach within a thematic analysis to explore how vegetarian identity is negotiated in the individuals’ different relationships and how this identity and lifestyle is understood by participants in relation to both the South African and wider global context. In particular, the intersection of vegetarian identity and other aspects of identity such as gender, ‘race’ and culture, was explored. The study found that some participants offered ethical reasons for their vegetarianism, including principled objections to consuming animals and not agreeing with the way animals are kept and bred to be eaten. Another finding was the disagreement within the participant group over whether vegetarianism was a healthier alternative to main-stream diets containing meat. The participants connected their experience and identity of vegetarianism to other alternative, marginal or less traditional identities, for example, expressing progressive and inclusionary views on homosexuality. Participants also strongly asserted progressive views on gender roles but these were contradicted by description of daily life in which traditional gender roles were maintained, particularly in relation to household tasks in the preparation of iv food .The contradictions in traditional South African identity was highlighted in that the (highly masculinised) ritual of the braai is asserted as defining “South African” culture across the divisive lines of ‘race’ but simultaneously, there is national pride in wildlife and the conservation of natural resources. The vegetarian community both physical and virtual was an important factor in relation to maintaining the vegetarian identity. The results revealed that participants generally avoid tension in their personal relationships. This avoidance was related to behaviour which worked to minimise conflict or potential tension. Participants displayed an overwhelming tolerance for meat-eaters’ diet despite their own strong views against eating meat.
A research project submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters in Psychology by Coursework and Research Report. University of the Witwatersrand, January, 2015